A CASE OF LOWER ANTERIOR PRIMARY TEETH FUSION - Noni Nurseni; Sri Hartini Soemartono; M. Fahlevi Rizal (Faculty of Dentistry, Universitas Indonesia, 2006)
Dental fusion is the most common problem seen in the primary dentition. The incidence of dental fusion was approximately 0.5% for deciduous dentition and 0.1% for permanent dentition. Fusion may be complete or incomplete. Its etiology was related to genetic or local factor. These anomalies could result in dental caries, esthetic problem, periodontal disease, dental malocclusion, and hypodontia in permanent dentition. Treatment of fused teeth depends on the location and extent of fusion. This report describes an incomplete dental fusion with dentinal caries occurred on 72 and 73 while 32 was agenesis. The purpose of the treatment was to improve the esthetic performance and subsequently to keep the teeth until the exfoliation time. After the restoration of 72 and 73, the patient feels satisfied.